Complex dynamics behavior analysis of a new chaotic system based on fractional-order memristor. Issue 1 (March 2021) - Qi, Yongwei; Wu, Chaojun; Zhang, Qi; Yan, Kai; Wang, Haohan
Abstract: In this paper, we propose a fractional-order active memristor based on fractional-order calculus, and its characteristics are analyzed. Combined with the new memristor, a fractional-order chaotic system is constructed. We study the complex dynamic behavior of the chaotic system by phase diagram, bifurcation diagram and Lyapunov exponential spectrum. The results show that with the change of fractional order and system parameters, the system will exhibit complex dynamic behaviors such as period, double period and chaos. With the change of initial values, the fractional system also exhibits the multistable characteristics of coexistence of different attractors. The research results show the complex dynamic behavior of fractional-order chaotic system.